Family function and eating behaviours among Hispanic/Latino youth: results from the Hispanic Community Children’s Health Study/Study of Latino Youth (SOL Youth) - Colón Ramos, Uriyoán (2020)
Objective: To elucidate mechanisms across family function, home environment and eating behaviours within sociocultural context among Hispanic youth. Design: Two models tested via path analysis (youth fruit and vegetable (FV) con- sumption; empty energy consumption) using data from the Study of Latino Youth (2011–2013). Setting: Chicago, IL; Miami, FL; Bronx, NY; San Diego, CA. Participants: Youth (8–16-year-olds), n 1466. Results: Youth ate 2·4 servings of FV per d and received 27 % of total energy from empty energies. Perceiving higher acculturative stress was indirectly associated with lower FV consumption via a pathway of low family function and family support for FV (β = −0·013, P < 0·001) and via lower family closeness and family support (β = −0·004, P = 0·004). Being >12-year-olds was indirectly associated with lower FV consumption via lower family closeness and family support (β = −0·006, P < 0·001). Household food security was indirectly associated with greater FV consumption via family closeness and family support (β=0·005, P = 0·003). In contrast, perceiving higher acculturative stress was indirectly associated with higher empty energy consumption (via family closeness and family support: β = 0·003, P = 0·028 and via low family function and low family support: β = 0·008, P = 0·05). Being older was associated with higher consumption of empty energies via family closeness (related to family support: β = 0·04, P = 0·016; parenting strategies for eating: β = 0·002, P = 0·049). Conclusions: Findings suggest pathways of influence across demographic and sociocultural context, family dynamics and home environment. The directionality of these associations needs confirmation using longitudinal data.